La Sicilia come metafora: Federico De Roberto e Tomasi di Lampedusa - Giannanti, Alessio (Studia Romanica Posnaniensia, 2014)
The aim of this work, taking into account the last critical lesson of C.A. Madrignani, is to reflect upon how Sicily has become, through literature, a metaphor of the national political condition, and how it paradigmatically represents the inability of Italy to change. More precisely its purpose is to investigate the contribution to the construction of national identity of authors like F. De Roberto and G. Tommasi di Lampedusa, whose “anti-historical” works are characterized by a desecrating description (sometimes even polemical) of the unification process of Italy. Even this illusory contradiction is part of the dimension referred to by Madrignani as the Sicily effect on Italian literature. In Viceré and Imperio (and even in the war novellas) De Roberto bluntly depicts Italian history as a fierce fight for power, where human egoism prevails, which, according to a pessimistic philosophy, denies any affirmation of positive values.